(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mobility Problem Is One Of The Concerning Matter For A Populated Country Like Indonesia. One Of The Simple Examples Of Mobility Problem Is Traffic Congestion. The Internet Penetration In Indonesia Is Growing Rapidly Day By Day And It Directly Affects The Growth Of Application Downloads. To Solve The Traffic Congestion, The Rate Of Downloading Traffic And Navigation Applications Increases. One Of The Most Popular Navigation Applications In Indonesia Is Waze. Waze Is The Biggest Community-Based Traffic And Navigation Application In The World. The Aim Of This Research Was To Analyze Factors Influencing The Continuance Intention Of Customers Towards Waze Application In Indonesia. A Research Model Used In This Study Was A Modified Unified Theory Of Acceptance And Use Of Technology 2 Model From Venkatesh Et. Al. With Content As A New Added Variable. The Data Were Gathered From 491 Respondents In Indonesia Chosen By Purposive Sampling Technique. The Results Revealed From The Highest To The Lowest Influence Consecutively Were Habit, Hedonic Motivation, Performance Expectancy, Price Value, And Social Influence. In Terms Of Moderating Factors, Age Only Moderated The Influence Of Performance Expectancy And Hedonic Motivation Toward Continuance Intention. This Modified Utaut2 Model Had A Strong Explanatory Power, Which Was 70.1%.